Republic of Armenia : Fourth Review under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report, 2003)
Armenia showed strong economic performance owing to its prudent macroeconomic policies and structural reforms, under the Poverty Reduction Growth Facility (PRGF) Arrangement. Executive Directors welcomed this development, and stressed the need to strengthen the tax system, structural reform agenda, and implement an effective anticorruption strategy. They emphasized the need to improve monetary stance, the legal financial sector framework, and banking supervision. They agreed that Armenia has successfully completed the fourth review under the PRGF program, and approved waiver.